FACTORES DE RIESGO ASOCIADOS A TUBERCULOSIS MULTIDROGORESISTENTE EN EL HOSPITAL II VITARTE ESSALUD DURANTE EL PERIODO ENERO DEL 2010 – DICIEMBRE 2016 - Bravo-Gutiérrez, Jason Hugo (2018)
Abstract   Objective: To identify the main risk factors associated with multidrug-resistant tuberculosis in patients who attend the Hospital II Vitarte EsSalud in the period January 2010 - December 2016. Methods: Observational, analytical, retrospective, cases controls study. The sample obtained was 164 patients with pulmonary tuberculosis in the Hospital II Vitarte EsSalud during the period January 2010 - December 2016, of which 41 were cases (MDR Tuberculosis) and 123 controls (Tuberculosis sensitive to first line drugs). A bivariate analysis was carried out using SPSS version 22.0, using the odds ratio calculation and the chi square test for analytical statistics. Results: The history of contact with a patient diagnosed with MDR tuberculosis, previous history of cured tuberculosis, history of abandonment of treatment, time of illness, history of diabetes mellitus and the history of alcohol and drug consumption were risk factors for the development of MDR tuberculosis. Conclusion: The risk factors to develop MDR tuberculosis are contact with MDR TB, previous history of cured tuberculosis, history of abandonment of treatment, time of illness, history of diabetes mellitus and the history of alcohol and drug consumption. Key words: multidrug resistant; Tuberculosis; Risk factor. (source: MeSH NLM DOI: https://doi.org/10.25176/RFMH.v18.n1.1263